The Influence of Job Satisfaction, Work Stress, And Career Development on Employee Turnover Intentions: JEL Classification: J28, M12, M54, J63, J24 - Rustam Taufik; A. Nur Insan; Abdul Samad Arief (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This paper will examine and discuss how job satisfaction, job stress, and career development affect turnover intention among the employees of the Muttaqin Bambang Purwanto Uswatun and Partners Public Appraisal Services Office in Jakarta. It follows a quantitative methodology. The sample population in this study was a population of 52 employees within the said office in Jakarta. The sampling method used was a saturated sampling method, where the entire population was covered with its total amount of 52 participants. The data was obtained by filling out a questionnaire using a Likert scale, which was provided by the means of Google Forms. This study findings show that the effect of job satisfaction on the turnover intention of the employees at the Muttaqin Bambang Purwanto Rozak Uswatun and Partners Public Appraisal Services Office in Jakarta is negative and statistically insignificant. Job stress positively and significantly influences the turnover intention of employees in the said office. The effects of career development on the turnover intention of employees in the same office, are positive albeit statistically significant. Additionally, job satisfaction, job stress, and career development are elements that determine turnover intention among the employees of the Muttaqin Bambang Purwanto Jakarta Office of the Purwanto Partners in Jakarta.